Production of SARS-CoV-2 virus-like particles as a vaccine candidate in stable cell lines through inducible E and M protein expression - Yu Liu; Zhian Chen; Li Yang; Chunmei Gan; Jieshi Tang; Zhaoyue Zheng; JingYa Ye; C. Alexander Valencia; Hoi Yee Chow; Biao Dong (BMC Biotechnology)
Abstract Virus-like particles (VLPs) offer potentially high-immunogenicity/low-cost vaccine platforms. SARS-CoV-2 VLPs production is achieved via transient transfection of genes encoding viral structural proteins, but is costly and difficult to scale up. To address this problem, stable VLPs-producing cell lines are desirable. In this study, we achieved efficient VLPs production by HEK293T cells after transient transfection of four plasmids containing the S, M, N, and E genes with optimized codons. Moreover, spike-specific IgG antibodies were elicited in mice, though no significant neutralizing activity was detected at the tested time points. Transmission electron microscopy (TEM) revealed that the VLPs diameters were approximately 120 nm. However, overexpression of E or M proteins was toxic to the cells. Stable cell lines were established by constructing two plasmids, in which E and M expression was controlled by an inducible Tet-on promoter and they were placed adjacent to S and N, respectively. A HEK293T cell line for stable expression of SARS-CoV-2 VLPs was established by co-selection with two antibiotics, puromycin and blasticidin. Specific IgG antibodies against the S protein were detected in mice immunized with VLPs formulated with the alum adjuvant. Our findings provide an effective approach for large-scale production of SARS-CoV-2 VLPs as vaccine candidates.